A survey of communication content in software requirements elicitation involving customer and developer - Che Pa, Noraini; Mohd Zain, Abdullah (IBIMA Publishing, 2011)
At the heart of software requirements elicitation lies the communication between customer and developer. There are several valuable components of communication such as medium, sender, receiver, and messages, which relates to the input and output from both parties. Most of these messages are delivered through incompletely, inconsistently or inaccurately defined communication medium. This study has been done to look into the communication content of the current communication practices between developer and customer in Malaysia. The results of this study revealed some important notes on the practices of communication content during software requirements elicitation process in Malaysia.